Fast Numerical Simulation of Two-Phase Transport Model in the Cathode of a Polymer Electrolyte Fuel Cell (Communications in Computational Physics, 2009)
In this paper, we apply streamline-diffusion and Galerkin-least-squares finite element methods for 2D steady-state two-phase model in the cathode of polymerelectrolyte fuel cell (PEFC) that contains a gas channel and a gas diffusion layer (GDL).This two-phase PEFC model is typically modeled by a modified Navier-Stokes equationfor the mass and momentum, with Darcy's drag as an additional source term inmomentum for flows through GDL, and a discontinuous and degenerate convection-diffusionequation for water concentration. Based on the mixed finite element methodfor the modified Navier-Stokes equation and standard finite element method for waterequation, we design streamline-diffusion and Galerkin-least-squares to overcomethe dominant convection arising from the gas channel. Meanwhile, we employ Kirchhofftransformation to deal with the discontinuous and degenerate diffusivity in waterconcentration. Numerical experiments demonstrate that our finite element methods,together with these numerical techniques, are able to get accurate physical solutionswith fast convergence.
Keywords: Two-phase model; polymer electrolyte fuel cell; Kirchhoff transformation; convection dominated diffusion problem; streamline diffusion; Galerkin-least-squares.